Influence of the use of recycled polyols obtained by glycolysis on the preparation of rigid polyurethane foam Influência do uso do poliol reciclado obtido pela glicólise na preparação da espuma rígida de poliuretano - Lopes E. (2012)
One of the major problems is the appropriate final destination of the materials or waste that can not be reused in the original process. Among the residues are rigid polyurethane foams, which are widely applied but difficult to reuse because they are thermosetting materials. The aim of this paper is to apply a chemical recycling process, glycolysis, and use the recycled polyol, product of glycolysis reaction, as part of the raw material for the formation of rigid polyurethane foams. Their mechanical properties and thermal conductivity were analyzed. The formation of foam cells with recycled polyol were evaluated by scanning electron microscopy (MEV). The results show that there is no loss of mechanical and thermal properties of PUR foam, satisfying the requirements for the production of domestic refrigerators.